2020
DOI: 10.21203/rs.3.rs-36238/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alveolar Neutrophilic Recruitment in COVID-19 May Not be Mediated by Th17 Response

Abstract: Introduction: The COVID-19 current pandemic disease differs from the H1N1pdm09 caused by Influenza A virus H1N1 subtype, by how it induces a pro-inflammatory response in infected lungs. Objective: Investigate the role of Th17 response in the pathogenesis of COVID-19 injury by analyzing the tissue expression of interleukins 8 and 17A and the neutrophils in lung samples of patients who die of COVID-19, comparing to H1N1pdm09. Study design and post-mortem results: Six lung samples from patients SARS-CoV-2 infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The miRNAs expression levels were significantly correlated with the expression of four of the seven inflammatory biomarkers previously analyzed (3,21,22) in the COVID-19 patients. MiR-26a-5p expression was observed inversely correlated with IL-6 tissue expression, one of the cytokines directly regulated by this miRNA (28).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The miRNAs expression levels were significantly correlated with the expression of four of the seven inflammatory biomarkers previously analyzed (3,21,22) in the COVID-19 patients. MiR-26a-5p expression was observed inversely correlated with IL-6 tissue expression, one of the cytokines directly regulated by this miRNA (28).…”
Section: Discussionmentioning
confidence: 82%
“…This clinical scenario is directly associated with the cytokine storm (8,9). Several studies, including from our collaborators, have shown an increase in the cytokines levels, and CASP-1 in patients with COVID-19 (3,8,9,21,22). The capillary-alveolar endothelial cells under the COVID-19 cytokines storm are activated and produce NF-κB and adhesion molecules such as ICAM-1 (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations